Preparation and Characterization Ni-Mo/Montmorillonite As A Catalyst In Cracking Process - Sopiarini, Putri; Firdaus, Firdaus; Taba, Paulina (Indonesian Journal of Chemical Research, 2015)
This research is aims to prepare and characterization of montmorillonite intercalated Ni-Mo as a catalyst in the cracking process. Preparation is do by extracting monmorillonite of bentonite by decantation method. Monmorillonite synthesized with NaCl to obtain Na-monmorillonite. Ni-Mo/monmorillonite obtained by dissolving ammonium hepta molybdate (NH4)6Mo7O24.4H2O) with distilled water and refluxed with Na-monmorillonite for 6 hours and dried at a temperature of 120oC. Furthermore, nickel nitrate hexahydrate (Ni(NO3)2.6H2O) is dissolved in distilled water and refluxed with Mo-monmorillonite for 6 hours and dried at a temperature of 120oC. Ni-Mo/monmorillonite obtained is then calcined at a temperature of 600oC for 4 hours to activate and eliminate the remnants of organic materials. Characterization of Ni-Mo/monmorillonite do by XRD, XRF and SEM. Characterization by XRD showing the change in the content of monmorillonite, Na-monmorillonite, and Ni-Mo/monmorillonite. Characterization by XRF confirms the success of the creators do with increasing metal content of Ni and Mo in monmorillonite replace the position of the metal Na. Characterization by SEM showed highly significant differences in morphology of montmorillonite, Na-monmorillonite and Ni-Mo-monmorillonite